Kerjasama Guru BK dan Guru Mata Pelajaran dalam Mengatasi Kesulitan Belajar Siswa di SMP Negeri 02 Mungka - Pertama, Momon Satria; Rahmi, Alfi (ALSYS, 2023)
Students behave unsupportively such as skipping class, lack of motivation and doing assignments. The collaboration between the BK teacher and the subject teacher only occurs regarding data such as academic grades or student achievement, students experience learning difficulties. The purpose of this study was to obtain information about the description of the forms of cooperation between the guidance counselor and subject teachers in overcoming student learning difficulties at SMP Negeri 02 Mungka. This research is descriptive qualitative, the sampling technique used is purposive sampling. The key informants were 1 counseling teacher and 2 subject teachers and supporting informants were students of SMP Negeri 02 Mungka. Data collection techniques with interviews and documentation. The analysis technique used is data reduction, data presentation, data verification, drawing conclusions. The data validation technique is data triangulation. The results showed that the form of cooperation between guidance and counseling teachers and subject teachers in helping to overcome learning difficulties was more in providing student data from guidance counselors and subject teachers in the form of written data regarding student values and behavior. It can be concluded that this collaboration depends on the problems faced by students and the frequency is also greater at the stages of student data collection, data processing and evaluation. The author's suggestion is that the Bk teacher and subject teachers should be more active in collaboration and open communication so that efforts are made to minimize learning difficulties in students.